2011
DOI: 10.1016/s1004-9541(11)60090-6
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Nano-MnFe2O4 and Its Catalytic Performance of Thermal Decomposition of Ammonium Perchlorate

Abstract: Nano-MnFe 2 O 4 particles were synthesized by co-precipitation phase inversion method and low-temperature combustion method respectively, using MnCl 2 , FeCl 3 , Mn(NO 3) 2 , Fe(NO 3) 3 , NaOH and C 6 H 8 O 7. X-ray diffraction (XRD), transmission electron microscope (TEM), Fourier transform infrared spectroscopy (FT-IR), thermogravimetry-differential thermal analysis (TG-DTA) and differential scanning calorimetry (DSC) were used to characterize the structure, morphology, thermal stability of MnFe 2 O 4 and it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 114 publications
(27 citation statements)
references
References 16 publications
2
22
0
Order By: Relevance
“…Besides, bimetallic oxide usually owns better catalytic activity for thermal decomposition of oxidants [19][20][21]. Several kinds of bimetallic iron oxides have been fabricated and used for thermal decomposition of AP [22][23][24][25][26][27][28]. These studies confirmed the catalytic activity of the ferrates for thermal decomposition of AP, however, most of the studies involved only single ferrate.…”
Section: Introductionmentioning
confidence: 88%
“…Besides, bimetallic oxide usually owns better catalytic activity for thermal decomposition of oxidants [19][20][21]. Several kinds of bimetallic iron oxides have been fabricated and used for thermal decomposition of AP [22][23][24][25][26][27][28]. These studies confirmed the catalytic activity of the ferrates for thermal decomposition of AP, however, most of the studies involved only single ferrate.…”
Section: Introductionmentioning
confidence: 88%
“…In accordance with published literatures, [23] 50 ml solution (0.3 mol/L −1 ) containing Fe (NO 3 ) 3 .9H 2 O and Mn (NO 3 ) 2 .4H 2 O with 2:1 volume ratio was prepared in deionized water and stirred continuously. Likewise, 50 ml of citric acid solution (0.3 mol/L −1 ) was prepared and the temperature reached to 70 C while stirring.…”
Section: Preparation Of Mnfe 2 Omentioning
confidence: 99%
“…Due to its perfect magnetic properties, it could help to recover synthesized nanocatalysts by a simple magnetic field. [22,23] In our study, MnFe 2 O 4 has been exploited as a substrate for immobilizing Keggin type POM to overcome the low surface-volume ratio and better recycling. [22] 2 | EXPERIMENTAL…”
Section: Introductionmentioning
confidence: 99%
“…where k 2 (g/mg min) is de ned as the pseudo-second-order adsorption constant rate and H (mg/g min) is de ned as initial adsorption rate (equation 4). Tables 1 and 2 show the parameters of these models and their respective values at ve CR concentrations (20,30,40,50, and 60 mg/L) by over EG@MnFe 2 O 4 and MnFe 2 O 4 , respectively. According to Table 1, which listed kinetic parameters of the CR adsorption models over EG@ MnFe 2 O 4 , the coe cients of determination R 2 for pseudosecond-order model (0.9987-0.9997) at all CR concentrations were far higher than those for pseudo-rst-order model (0.8396-0.9749), indicating that the predicted data were well tted with experimental data.…”
Section: E Ect Of Contact Time and Adsorption Kineticsmentioning
confidence: 99%